Biological effects of lithium on the structure of the liver in conditions of remote tumor growth - Bakhbayeva, S.A.; Bgatova, N.P.; Zhumadina, Sh.M. (Fundamental and Experimental Biology, 2019)
In the experiment on CBA mice the effect of lithium carbonate on the liver structure when used as an antitumor agent was studied. Tumor growth was modeled by introducing hepatocarcinoma-29 cells into the muscle tissue of the right thigh of experimental animals. Lithium carbonate was administered on the periphery of tumor growth at a dose of 0.037 mg per animal. The structure of the liver was studied by light, electron microscopy and morphometry after 3, 7, 13, and 30 days of the experiment. In the dynamics of remote tumor growth, structural changes in the liver were discovered, which indicates the organ dysfunction. It has been shown that by the 30th day of tumor development there was a decrease in the volume and number density of hepatocytes, a decrease in the number density of binuclear cells and an increase in the volume density of sinusoids. In hepatocytes there was a decrease in the concentration of all intracellular organelles, which is a reflection of a decrease in the energy and synthetic function of cells. The use of lithium carbonate as an antitumor agent led to the aggravation of structural changes in the liver, which was apparently due to an increase in the toxic load on the organ due to an increase in the decay products and the dying of tumor cells under the influence of lithium.